THE AESTHETICS OF CARVING MOTIFS IN WOOD DECORATIVE WORKS AS A MEDIUM OF EXPRESSION BY CRAFTSMEN IN JEPARA - Shelfi Anindia Angelia; Wasis Wijayanto (Eduarts: Jurnal Pendidikan Seni, 2025)
The art of Jepara wood carving is part of the cultural wealth of the archipelago that has aesthetic value, symbolic meaning, and history. This art is also important in shaping the cultural identity of the Jepara people. With the development of globalization and the creative industry, there is a change in the way artisans make carving art, especially in terms of creativity, production methods, and the role of art itself. This research aims to analyze the creativity of artisans, study the art of carving in the context of the creative industry, as well as understand the changes in the function of the art of carving in Mulyoharjo Village, Jepara Regency. This research uses a qualitative method with a case study approach. Data was collected through observation, in-depth interviews, and work documentation, then analyzed with the Miles and Huberman models. Research results show that the creativity of artisans can be seen from the development of motifs, shape variations, and the combination of traditional elements and modern design. The art of Jepara carving continues to grow as part of the creative industry that leads to the market, but still maintains the local cultural heritage. The change in the function of carving can be seen from the shift in the role of the work, from symbolic objects to decorative products and economic goods that help the survival of artisans